Performa Pertumbuhan dan Kelulushidupan Udang Vaname (Litopenaeus vannamei) yang Dipelihara pada Salinitas Rendah - Supono, Supono; Turovika, Yeti Barokah; Hudaidah, Siti (Journal of Tropical Marine Science, 2024)
Vaname shrimp (Litopenaeus vannamei) is one of Indonesia's leading cultivation commodities in the fisheries sector. The success of the vaname shrimp cultivation business cannot be separated from the water quality parameters, which play a role in supporting their growth and survival rate. Salinity is a water quality variable that plays a very important role in the growth and survival of Vannamei shrimp. The aim of this research was to study the growth and survival rate of vaname shrimp reared at low salinity. The research design used was a completely randomized design consisting of three treatments and four replications. These treatments had media salinities of 1 ppt, 3 ppt, and 5 ppt. Shrimp rearing is carried out in a 40-liter volume container with a stocking density of 40 fish per container, or 1 PL/L. Shrimp farming is carried out for 35 days. The observation parameters carried out during this research were Specific Growth Rate (SGR), Growth Rate (GR), Survival Rate (SR), Feed Conversion Ratio (FCR), Total Vibrio Count (TVC), and water quality in the maintenance media. The research results showed that media salinity of 3 and 5 ppt was the best treatment for increasing the growth and survival rate of vaname shrimp.